Examining the determinants of tax arrears: Evidence from Malaysia - Hamid, Zarinah; Radzuan, Neazlin (Global Academic Research, 2017)
The objective of this paper primarily aims to determine the factors influencing tax arrears amongst Malaysian tax payers by using demographic variables such as: age, gender, marital status, education, income and occupation as explanatory variables. It is conducted with an aim to complement prior research through exploring possible relationship between tax compliance behaviour and tax arrears. A number of previous literatures are cited in view to confirm the relationship among these variables. Based on the analysis of the available data, this study employs a multiple regression approach for 3,469 observations which are extracted from the national survey commissioned by IRB in 2011. A stepwise backward elimination method is utilized. The results show that gender, marital status, education and occupation are statistically insignificant at 5% level. Meanwhile two explanatory variables, i.e. age and income level are found to be statistically significant and able to explain tax arrears. Conclusion is then deduced that a negative relationship is observed between tax compliance behaviour and tax arrears. To improve future research, the use of secondary data is proposed for more accurate analysis. There is also an opportunity to broaden similar research to other tax related components and sectors which are still remained unexplored such as tax rates, audit probabilities and penalty structures.